1997
DOI: 10.1021/ma9615866
|View full text |Cite
|
Sign up to set email alerts
|

“Living” Free-Radical Polymerizations in the Absence of Initiators:  Controlled Autopolymerization

Abstract: The autopolymerization of styrene, styrenic derivatives, and styrene/(meth)acrylate comonomer mixtures in the presence of stable nitroxide free radicals has been shown to be a “living” process. Molecular weight can be controlled by varying the ratio of vinyl monomer to TEMPO and low-polydispersity materials are obtained. Significantly, a definite incubation period is observed during these polymerizations, and the length of this incubation period increases with increasing amounts of TEMPO. The structures of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
120
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 15 publications
8
120
2
Order By: Relevance
“…The observed trend is irregular or fluctuating. This result is in contrary to the observation of Devonport et al [13] who previously showed that the number of average molecular weights increased in an almost linear fashion with conversion. They revisited the thermal initiation of styrene in the presence of TEMPO at 125°C after conflicting results were reported almost simultaneously ) and found that the number-average molecular weights did not vary significantly with conversions.…”
Section: Kinetic Model Development For Monomer Conversioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The observed trend is irregular or fluctuating. This result is in contrary to the observation of Devonport et al [13] who previously showed that the number of average molecular weights increased in an almost linear fashion with conversion. They revisited the thermal initiation of styrene in the presence of TEMPO at 125°C after conflicting results were reported almost simultaneously ) and found that the number-average molecular weights did not vary significantly with conversions.…”
Section: Kinetic Model Development For Monomer Conversioncontrasting
confidence: 99%
“…Tefera et al [12] also investigated, both experimentally and theoretically, the free-radical suspension polymerization of styrene at different temperatures (i.e., 70°C, 75°C, and 80°C) and initiator concentrations [i.e., azobis-isobutyronitrile (AIBN): 0.15-0.45 wt% of styrene]. Devonport et al [13] revisited the thermal initiation of styrene in the presence of 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) at 125°C. They showed that low polydispersities and controlled molecular weights could be achieved under these conditions, although the degree of control was not as good as for unimolecular or bimolecular initiating systems.…”
Section: Introductionmentioning
confidence: 99%
“…monomers [17][18][19][20][21]; however, the scope of the applicable monomers has been extended by improving the structure of the nitroxide [22][23][24] using alkoxyamine adducts [25,26] and utilizing additives [27,28]. The NMP still has advantages in using nonmetallic catalysts, thus creating a great variety of architectures through designing the nitroxide catalysts, and producing uncolored or less-colored polymers.…”
Section: Open Accessmentioning
confidence: 99%
“…Polymers of welldefined structure and properties can be obtained using the advanced synthetic techniques, such as nitroxide-mediated radical polymerization (NMRP) [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. A quasiliving polymerization takes place at elevated temperatures (usually above 100 o C) in mixtures containing monomer, a thermal initiator [(dibenzoyl peroxide, 2,2΄-azobis(isobutyronitrile)] and a nitroxide stable radical.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of the conjuction of thermal initiator with nitroxide, an alkoxyamine-based unimolecular initiator carrying both a latent initiating group and nitroxide in the 1:1 mole ratio can be used [10,15]. Some monomers and monomer pairs (styrene, styrene maleimide or styrene Nsubstituted maleimide derivative) polymerize in the quasiliving manner even without any added initiator, only in the presence of nitroxide [5,16,17]. The mediating role of the nitroxide consists in reversible termination of growing polymer chains under formation of thermally unstable N-alkoxyamine bonds.…”
Section: Introductionmentioning
confidence: 99%